LEVELS OF STUDENTS’ ANXIETY TOWARDS ENGLISH TEACHING THROUGH SONGS - Meliyana Imelda; Junia Fajardini (IKIP Siliwangi, 2018)
This study entitled “LEVELS OF STUDENTS’ ANXIETY TOWARDS ENGLISH TEACHING THROUGH SONGS” was to observing students’ anxiety levels through the songs. In this case, the writers compared levels of students’ anxiety in English teaching with songs and English teaching without songs. The participants were two classes consisted 30 students, 15 students from XI Putra and 15 students from XI Putri. The data in this study were collected by giving Foreign Language Classroom Anxiety Scale questionnaire by Horwitz et al (1986). The FLCAS questionnaire consisting of 33 items scoring with Likert’s scale and analyzed manually used Oetting’s scale to categorize anxiety levels. The study showed that there was a significant difference between class that used English songs method and class without used English songs method. The class with songs was relaxed while the class without songs was mildly anxious.Keywords: Songs, English Songs, Anxiety